Anesthetic Complications and Deaths - Pender, John W. (1968)
Anesthesiologists should fully inform patients of the possible complications from anesthesia. For rapport with the patient, with whom they usually have no acquaintance until a day or so before an operative procedure, the anesthesiologist should enlist the help of the internist or surgeon who already has established an atmosphere of trust. The extent of morbidity and minor complications from anesthesia has not been adequately recorded. One out of every 1,000 to 2,000 anesthetized patients dies of complications primarily due to or contributed to by anesthesia. Leading causes of death vary from study to study and from year to year.